Silence of the jams - Leeson, Gayle, 1967- (Leeson, Gayle, 1967- Down South Café mystery., 2017)
In the latest Southern cozy from the author of The Calamity Cafe, small-town chef Amy Flowers can't take her freedom for granted when she's served up as a murder suspect ... ' It's Independence Day in Winter Garden, Virginia, and the residents are gearing up for their annual celebration. The Down South Cafe is open and flourishing, and Amy Flowers is busy making pies and cakes for the holiday. The only thorn in her side is Chamber of Commerce director George Lincoln, who is trying to buy the cafe so he can tear it down and build a B & B on the site. When George collapses while eating at the Down South, everybody assumes it's a heart attack-until the autopsy declares it to be poisoning. Now, it's up to Amy to prove her innocence before her liberty is lost. Includes delicious Southern recipes!